2013
DOI: 10.1017/s0950268813002203
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse pregnancy outcome in women exposed to livestock: a study within the Danish National Birth Cohort

Abstract: SUMMARYMaternal infection in pregnancy is a known risk factor for adverse pregnancy outcome, and a number of zoonotic pathogens may constitute a risk to pregnant women and their fetuses. With animal contact as a proxy for the risk of zoonotic infection, this study aimed to evaluate pregnancy outcome in women with self-reported occupational or domestic contact with livestock compared to pregnant women without such contact. The Danish National Birth Cohort collected information on pregnancy outcome from 100 418 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…No association was found between exposure to goats and raw goat products with adverse pregnancy outcomes in our study, which was similar to the findings of a large cohort study from Denmark, although the study designs and methodologies were different. Compared to our study, the Denmark study focused on a wide variety of animals rather than goats only, and short duration for notification of exposure collected and the study reported lower rate of cutaneous contact [32]. Although approximately one-third of the women in our study said they had been exposed to goats and raw goat products at least one time before this current pregnancy, they were less likely to be exposed during pregnancy as also found in previous studies [3335].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…No association was found between exposure to goats and raw goat products with adverse pregnancy outcomes in our study, which was similar to the findings of a large cohort study from Denmark, although the study designs and methodologies were different. Compared to our study, the Denmark study focused on a wide variety of animals rather than goats only, and short duration for notification of exposure collected and the study reported lower rate of cutaneous contact [32]. Although approximately one-third of the women in our study said they had been exposed to goats and raw goat products at least one time before this current pregnancy, they were less likely to be exposed during pregnancy as also found in previous studies [3335].…”
Section: Discussionmentioning
confidence: 87%
“…This was likely related to ritual Islamic activities as the majority of our participants were Muslim, such as “Aqeeqah”, the ritual animal sacrifice on the occasion of a new birth, and “Qurbani”, the Islamic religious practice of an animal sacrifice offering to Allah [47]. Good hand hygiene practicing among people having extensive exposure to animal raising or contaminated environments and avoiding food-borne zoonosis by cooking meat well or boiling milk before consuming them should be promoted [32, 48]. For women, an explanation of the dangers involved with being around goats can be explained during ANC visits; however, a previous study found a low rate of healthcare providers gave information about hand or food hygiene for their patients who exposed to animals [49].…”
Section: Discussionmentioning
confidence: 99%